2022
DOI: 10.1002/elsc.202200030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metals on the regulation of acidogenic metabolism enhancing biohydrogen and carboxylic acids production from brewery spent grains: Microbial dynamics and biochemical analysis

Abstract: The present study reports the mixed culture acidogenic production of biohydrogen and carboxylic acids (CA) from brewery spent grains (BSG) in the presence of high concentrations of cobalt, iron, nickel, and zinc. The metals enhanced biohydrogen output by 2.39 times along with CA biosynthesis by 1.73 times. Cobalt and iron promoted the acetate and butyrate pathways, leading to the accumulation of 5.14 gCOD/L of acetic and 11.36 gCOD/L of butyric acid. The production of solvents (ethanol + butanol) was higher wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…To enhance the productivity of caproic acid, the microbial process needs proper investigations and regulation considering the influential factors. 36,50…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To enhance the productivity of caproic acid, the microbial process needs proper investigations and regulation considering the influential factors. 36,50…”
Section: Resultsmentioning
confidence: 99%
“…This finding is corroborated by the previous studies that demonstrated Clostridium sensu stricto as the primary hydrogen producer and have observed a correlation between its abundance and hydrogen yield. 36,57,58 Yang and Wang examined microbial community structure changes in dark fermentative hydrogen generation and found that Clostridium sensu stricto 1 contributed more to hydrogen production. 59 Kumar et al used experimental design to determine optimum hydrogen generation settings and discovered that Clostridium sp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations